Crocin improves post-thaw quality, fertility-associated gene expression and fertilization potential of buffalo bull sperm - Amjad Riaz; Ghulam S. Khan; Muhammad Zahid Tahir; Muhammad Yasir Zahoor; Hifz-ul-Rahman Hifz-ul-Rahman (Revista Científica)
Buffalo sperm suffer more cryoinjuries due to lipid peroxidation of their high structural polyunsaturated fatty acid contents than cattle. Consequently, the post-thaw fertilization potential of buffalo sperm is compromised. Crocin is a carotenoid known for its antioxidant potential through scavenging reactive oxygen species. The current study investigated the effect of crocin addition in the semen extender on the post-thaw quality, fertility- associated gene expression, and fertilization potential of buffalo bull sperm. Semen samples (n=32) from four Nili-Ravi buffalo bulls were extended with tris-citric acid extender containing different concentrations of crocin (0mM; control, 0.5, 1, 1.5, and 2mM). The extended semen was packed in 0.5 mL French straws (25 x 10 6 sperm/ straw) and cryopreserved using liquid nitrogen vapor freezing protocol. Computer-assisted semen analysis, Normal Apical Ridge assay, Rhodamine 123, Acridine orange, and Propidium iodide staining were used to assess sperm motility parameters, acrosome integrity, mitochondrial membrane potential, DNA integrity, and viability, respectively. Expression levels of sperm acrosome-associated SPACA3, DNA condensation-related PRM1, anti- apoptotic BCL2, pro-apoptotic BAX, and oxidative stress-associated ROMO1 genes were evaluated through qPCR. The in vivo fertility of semen doses containing 1mM crocin was compared with control. Buffaloes were inseminated 24 hours after the onset of natural estrus and transrectally palpated for pregnancy at least 60 days post-insemination. Data were analyzed through PROC MIXED or PROC GLIMMIX using SAS. Tukey test was applied for multiple comparisons among treatments. Post-thaw evaluation revealed that 0.5 and 1mM crocin improved total motility, plasma membrane integrity, acrosome integrity, mitochondrial membrane potential, and viability, and one and 1.5mM crocin enhanced catalase activity and reduced lipid peroxidation compared to control (p<0.05). Moreover, 1mM crocin improved progressive motility, kinematics, and DNA integrity than control (p<0.05). Expression levels of SPACA3, PRM1, and BCL2 genes were higher (p<0.05) with 1mM crocin, whereas no difference (p>0.05) was observed in the expression of BAX gene among all groups. Moreover, ROMO1 gene expression was higher (p<0.05) with 2mM compared to 1mM and 1.5mM crocin. Semen doses containing 1mM crocin showed a higher fertility rate compared to control [56±0.03% (112/200) vs. 46±0.04% (92/200), respectively; p=0.0465]. In conclusion, 1mM crocin addition in the semen extender improves post-thaw quality, fertility-associated gene expression, and fertilization potential of buffalo bull sperm.